دور إدارة المعرفة في تحقيق الإبداع : دراسة تحليلية لآراء عينة من التدريسيين في المعهد التقني الموصل - على، جعفر خليل مرعى Ali, Jaafar Khalil Marei; نجم، أحمد ثامر (جامعة الأنبار - كلية الإدارة والاقتصاد, 2013)
‏إدارة المعرفة في المنظمات بشكل عام والمنظمات التعليمية بشكل خاص تمثل مدخلاً فعالاً لتحقيق الإبداع من خلال التشخيص والقياس لتلك الإبداعات وتوضيح أنواعها، إذ تمثل إدارة المعرفة قاعدة العمل في المنظمات فضلاً عن أنه أداة فاعلة تسترشد بها القيادات الإدارية، عليه فإن إدارة المعرفة تترك مديات وتقر تأثيرات في الأنشطة المنظمية وهذه الأنشطة موضع تأثر لما ‏هو محدق بالمنظمات من تغييرات وهذه الحالة تعبر عن أهمية إدارة المعرفة ودورها في تحقيق الإبداع حالياً ومستقبليا، هذه قادتنا إلى دراسة الموضوع في منظمة تعليمية متمثلة بالمعهد التقني الموصل عن طريق اختيار عينة عشوائية مكونه من (30‏) تدريسياً في تلك المنظمة، وتم اعتماد منهجية أشرت مشكلة ووضحت أهدافها وسعت إلى اختبار فرضياتها وقد توصلت الدراسة إلى جملة استنتاجات منها وجود علاقة ارتباط وأثر ذو دلالة معنوية بين بعدي الظاهرة قيد الدارسة واعتمادا على ذلك خرجت الدراسة بعده توصيات مهمة. Knowledge Management in the organizations in general and in educational organizations in particular represents an effective approach to achieve of Innovation \ through diagnosing and measuring those innovation and explaining its kinds. \ Knowledge management represents a base of work in organizations. More over it is an effective tool as guided for managerial leaderships. So knowledge management imposes effects on the organizational activities. These activities are affected by what surrounds the organizations of changes. This condition is an indication to theimportance of knowledge management and it's role in achieving innovation in present and in the future. \ This situation lead us to study this subject in an educational organization represented by the Technical Institute in Mosul, through collecting a random sample of (30) teachers in the mentioned organization. The study depended a methodology which indicate the problem of the study, explained it's goals and aimed to verify its hypotheses. The study concluded to some conclusions such as there are a significant correlation and effects relationship between the two dimensions of the study as well as providing some important recommendations.
808375
Keywords: العراق -- إدارة المعرفة -- التفكير الإبداعي -- هيئة التدريس -- المعهد التقني -- الموصل